Multifunctional cement pastes with ZnO.CoO and barium ferrite core-shell nanostructures: mechanical, antimicrobial, and radiation shielding properties - Mahmoud Gharieb; H.M. Khater; Wageeh Ramadan; Walaa M. Abd El-Gawad (Next Materials, 2025)
The research explores innovative multifunctional cement pastes by integrating modified blast furnace slag by precipitating a thin layer of nano-ZnO.CoO or nano-barium ferrite on its surface, forming core-shell structures (ZnCo-slag and BaFe-slag), aiming to provide enhanced mechanical properties alongside antimicrobial and radiation shielding capabilities. Key findings reveal that cement pastes with 10 % ZnCo-slag achieved a notable 6 % increase in mechanical strength over 5 % ZnCo-slag and a 3 % advantage over 15 % ZnCo-slag. Moreover, cement pastes with 10 % BaFe slag increased the strength by 4 % and 5 % over the mixes containing 5 % BaFe slag and 15 % BaFe slag, respectively. In terms of antimicrobial activity, ZnCo-slag exhibited significant inhibition zones of 15 mm, 17 mm, and 25 mm against Escherichia coli, Staphylococcus aureus, and Candida albicans, respectively, while BaFe-slag surpassed these with zones of 11 mm, 20 mm, and 26 mm. Additionally, the 10 % BaFe-slag formulation demonstrated exceptional gamma radiation attenuation, improving by 11.8 % at 0.662 MeV, 13.2 % at 1.173 MeV, and 10.8 % at 1.333 MeV compared to ordinary Portland cement. This study highlights the potential of repurposing blast furnace slag into advanced materials that not only enhance mechanical strength but also provide antimicrobial properties and effective radiation shielding, combining sustainability with cost efficiency.